Scandals of Misreading: Serial Killer Shockers and Imaginative Resistance - Vanhanen, Tero Eljas (MDPI, 2026)
In the winter of 1991, the frenzied scandal around Bret Easton Ellis’s serial killer smash American Psycho overshadowed another, no less serious literary controversy. Published less than two months after Ellis’s blockbuster, Dennis Cooper’s transgressive queer classic Frisk may have been largely ignored in mainstream cultural outlets, but in the queer community the scandal was deadly serious. Seemingly connecting queer sexuality with serial murder and pedophilia, the novel incited intensely angry demands for censorship. The controversy culminated in a very public death threat against Cooper from members of Queer Nation, a gay rights group known for its shock tactics. The critical response has mostly dismissed the scandals surrounding the novels as based on a particular kind of misreading or misinterpretation. Both works use similar narrative strategies to shock and scandalize their audience but aim to mitigate this response through the strategic use of unreliable narration. While scholars have often made the argument that the violence in the novels should be interpreted as mere fantasies of their unreliable narrators, this kind of nuanced interpretation was wholly absent in the scandalized response to the novels. The common critical defense, however, is itself based on a misunderstanding of the scandals. Fictionality and narrative reliability as such have little to do with the responses of imaginative resistance and moral disgust prompted by the representation of extreme violence. In this article, I analyze and compare the public and scholarly receptions of the novels, highlighting how scholarly discourse has often overlooked how the novels anticipated and aimed to incite the scandalized public response they ultimately provoked. © 2025 by the author.